Antero-posterior position of the cleat for road cycling - Ramos Ortega, J.; Munuera, P.V.; Dominguez, G. (Science & Sports, 2012)
Objective: This work aims at determining the antero-posterior position of the cleat based on various morphological characteristics of the cyclist's lower limb.